The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/14786419.2019.1700507
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharide from Caulerpa lentillifera: extraction optimization with response surface methodology, structure and antioxidant activities

Abstract: Ultrasonic-assisted extraction based on Response SurfaceMethodology was applied to isolate a polysaccharide (CLP) from Caulerpa lentillifera obtained in the South China Sea and the highest yield of the crude polysaccharide was 11.8%. CLP consisted of xylose, galactose, glucose and glucuronic acid in a molar ratio of 2.00: 1.00: 0.26: 0.04, with a molecular weight of 115 kDa. The content of uronic acids and sulfate groups in CLP was 14.10% and 27.40%, respectively. CLP presented good radical scavenging activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
0
12
0
6
Order By: Relevance
“…Hot water extract from C. racemosa showed antiviral and antioxidant activities. Several polysaccharides extracted from Caulerpa have shown antioxidant activities: the C. lentillifera polysaccharide produced by ultrasonic-assisted extraction presented good radical scavenging activities against the DPPH radical [97]. The C. lentillifera polysaccharide antioxidant activity might be influenced by sulfate and uronic acid contents [97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hot water extract from C. racemosa showed antiviral and antioxidant activities. Several polysaccharides extracted from Caulerpa have shown antioxidant activities: the C. lentillifera polysaccharide produced by ultrasonic-assisted extraction presented good radical scavenging activities against the DPPH radical [97]. The C. lentillifera polysaccharide antioxidant activity might be influenced by sulfate and uronic acid contents [97].…”
Section: Discussionmentioning
confidence: 99%
“…Several polysaccharides extracted from Caulerpa have shown antioxidant activities: the C. lentillifera polysaccharide produced by ultrasonic-assisted extraction presented good radical scavenging activities against the DPPH radical [97]. The C. lentillifera polysaccharide antioxidant activity might be influenced by sulfate and uronic acid contents [97]. Fernando et al [33] reported DPPH activity, with an IC 50 of >2 mg/mL, of a polysaccharide extracted from C. racemosa.…”
Section: Discussionmentioning
confidence: 99%
“…C. lentillifera is a low-energy food with high contents of dietary fibers, and its polysaccharide content is as high as ≥40% (dry weight) ( Zhang et al, 2020 ). Sulfated polysaccharides isolated from C. lentillifera (CLSPs) have been reported to have antioxidant ( Tian et al, 2019 ), anti-diabetic ( Khairuddin et al, 2020 ), and anticancer activities ( Maeda et al, 2012 ). Moreover, a homogeneous fraction, CLGP4, with the monosaccharide composition of Xyl, Man, and Gal in a percentage ratio of 1.00:2.15:2.40 and a molecular weight of 3877.8 kDa exhibited immunostimulatory effect ( Sun et al, 2018 ; Sun et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that the constituent monomers of C. lentillifera from the South China Sea consisted of xylose, galactose, glucose and glucuronic acid (Tian et al 2019). Mannose, galactose, glucose and xylose are the constituent monomers of sulfated polysaccharides in the extracts of C. lentillifera from Phetchaburi Province, Thailand (Chaiklahan et al 2020).…”
Section: Monosaccharide Compositionmentioning
confidence: 99%